GSK3β and mTORC1 Represent 2 Distinct Signaling Markers in Peripheral Blood Mononuclear Cells of Drug-Naive, First Episode of Psychosis Patients. (27th June 2022) - Petrikis, Petros; Polyzou, Alexandra; Premeti, Kyriaki; Roumelioti, Argyro; Karampas, Andreas; Georgiou, Georgios; Grigoriadis, Dionysios; Leondaritis, George
Abstract: Background and Hypothesis: Schizophrenia is characterized by a complex interplay between genetic and environmental risk factors converging on prominent signaling pathways that orchestrate brain development. The Akt/GSK3β/mTORC1 pathway has long been recognized as a point of convergence and etiological mechanism, but despite evidence suggesting its hypofunction, it is still not clear if this is already established during the first episode of psychosis (FEP). Study Design: Here, we performed a systematic phosphorylation analysis of Akt, GSK3β, and S6, a mTORC1 downstream target, in fresh peripheral blood mononuclear cells from drug-naive FEP patients and control subjects. Study Results: Our results suggest 2 distinct signaling endophenotypes in FEP patients. GSK3β hypofunction exhibits a promiscuous association with psychopathology, and it is normalized after treatment, whereas mTORC1 hypofunction represents a stable state. Conclusions: Our study provides novel insight on the peripheral hypofunction of the Akt/GSK3β/mTORC1 pathway and highlights mTORC1 activity as a prominent integrator of altered peripheral immune and metabolic states in FEP patients.